Meningkatkan Partisipasi Siswa Kelas VIII dalam Pembelajaran PAK melalui Metode PBL Fase D - Kasimo Kasimo; Nerita Setianingtyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to address the low student participation in Catholic Religious Education (CRE) learning in class VIII of SMP St. Fransiskus II, East Jakarta. Preliminary observations revealed students’ lack of engagement in class discussions, presentations, and group activities, which is suspected to result from the continued use of conventional teaching methods. To overcome this, the study implements the Problem-Based Learning (PBL) method, which emphasizes contextual problem-solving and student-centered learning. Using the Classroom Action Research (CAR) model, the study was conducted in two cycles consisting of planning, action, observation, and reflection stages. Learning activities were designed based on the PBL approach. Data were collected through observation sheets focused on student participation indicators such as discussion activeness, presentation ability, group collaboration, and task completion. Quantitative data were analyzed descriptively, while qualitative data from teacher reflections and field notes were used to explore learning dynamics. The findings showed a notable improvement in student participation: from 65% in the first cycle to 85% in the second. All indicators improved, including more active involvement in discussions, better presentation quality, and timely task completion. Qualitative data supported these results, showing increased student motivation, enthusiasm, and collaboration. In conclusion, the implementation of the PBL method effectively enhanced student participation in CRE learning. It not only increased activeness but also supported the development of critical thinking, collaboration, and communication skills. The study suggests PAK teachers consider adopting the PBL method to improve engagement and learning outcomes.